Icelandic Strategic Culture: And The Formation of Icelandic Foreign Policy - Jónatan Þór Halldórsson 1986- (2016)
The objective of this thesis is to make a case for Icelandic strategic culture and to illustrate how strategic culture has influenced Icelandic foreign policy throughout the years. Few, if any, attempts have been made to provide a holistic understanding of Icelandic strategic decisions. In this thesis, I will test hypotheses that I have constructed based on two IR theories; Strategic culture, and neorealism. Three cases are then analyzed: Iceland’s entrance into NATO, the bilateral defense agreement with the US and the US withdrawal from Iceland in 2006. Strategic culture maintains that there is a connection between strategic culture and strategic decisions, that there are cultural explanations behind decisions taken by governments in order to secure themselves. On the other hand, neorealism argues that states make decisions based on their relative capabilities to other states in order to maximize their security. My conclusion is that Iceland does indeed have a strategic culture and that strategic culture is better qualified to explain Iceland’s strategic decisions. Furthermore, strategic culture has played a vital role in the shaping of Iceland’s foreign policy in the 20th century and is better suited to give a holistic understanding on Iceland’s decision making than neorealism. Markmið þessarar ritgerðar renna stoðum undir íslenska (strategíska) menningu og að sýna hvernig hún hefur haft áhrif á íslenska utanríkisstefnu í gegnum árin. Fáar, jafnvel engar, tilraunir hafa verið gerðar til þess að veita heildstæðan skilning á íslenskum strategískum ákvörðunum. Í þessari ritgerð mun ég prófa tilgátur sem ég hef sett fram út frá tveimur kenningum alþjóðasamskipta; strategískri menningu og nýraunhyggju. Þrjú tilvik verða til skoðunar; þau eru inngangan í NATO, Varnarsamningurinn við Bandaríkin og brotthvarf Bandaríkjamanna frá Íslandi 2006. Strategísk menning heldur því fram að það sé samband á milli strategískrar menningar og strategískra ákvarðana. Með öðrum orðum, að til séu menningarlegar útskýringar á ...